2022
DOI: 10.1186/s12937-022-00806-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary total antioxidant capacity in relation to metabolic health status in overweight and obese adolescents

Abstract: Background Although several studies evaluated the relationship between individual dietary antioxidants and metabolic health conditions, data on the association between dietary total antioxidant capacity and metabolic health among children and adolescents is limited. This study investigated the relationship between dietary total antioxidant capacity and metabolic health status in Iranian overweight/obese adolescents. Methods This cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
(67 reference statements)
1
5
0
Order By: Relevance
“…62,63 Interventions of antioxidants/reduced oxidation process could decrease such adverse health effects. 64,65 In this connection, Ganoderma lucidum polysaccharides have shown to reduce AGEs in the high fat diet-fed rats; 66 similar results were observed with our study wherein AGEs reduced in the e-GAGfed treatment groups.…”
Section: Food and Function Papersupporting
confidence: 89%
“…62,63 Interventions of antioxidants/reduced oxidation process could decrease such adverse health effects. 64,65 In this connection, Ganoderma lucidum polysaccharides have shown to reduce AGEs in the high fat diet-fed rats; 66 similar results were observed with our study wherein AGEs reduced in the e-GAGfed treatment groups.…”
Section: Food and Function Papersupporting
confidence: 89%
“…HEI-2015 is a diet quality index that measures the consistency of dietary guidelines for Americans [ 9 ]. Dietary quality assessed by HEI-2015 has been shown to be positively correlated with antioxidant capacity [ 9 , 29 ]. According to the International Diabetes Federation (IDF) criteria, the higher the dietary antioxidant intake, the lower the likelihood of developing obesity [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary quality assessed by HEI-2015 has been shown to be positively correlated with antioxidant capacity [ 9 , 29 ]. According to the International Diabetes Federation (IDF) criteria, the higher the dietary antioxidant intake, the lower the likelihood of developing obesity [ 29 ]. However, this study found no significant association between the AHEI-2010 score and the risk of overweight/obesity in children, which may be related to the sample size included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies investigated the association between dietary antioxidants and BMI in adolescents. 22 , 23 , 30 Imboden et al. reported that there was no association between antioxidant intake and BMI in children.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies investigated the association between dietary antioxidants and BMI in adolescents 22,23,30 . Imboden et al.…”
Section: Discussionmentioning
confidence: 99%